2008
DOI: 10.1080/13598660801971625
|View full text |Cite
|
Sign up to set email alerts
|

Teachers working in culturally diverse classrooms: implications for the development of professional standards and for teacher education

Abstract: Teachers working in culturally diverse classrooms: implications for the development of professional standards and for teacher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Our review indicates that there is a paucity of information about the kind of experiences that would be most useful in an OSPEX program. In a more recent analysis, Thomas & Kearney (2008) argued that there is a link between cultural awareness and confidence in teaching, and this link needs to be explored in both domestic and OSPEX contexts.…”
Section: The Emerging Global Context Of Professional Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Our review indicates that there is a paucity of information about the kind of experiences that would be most useful in an OSPEX program. In a more recent analysis, Thomas & Kearney (2008) argued that there is a link between cultural awareness and confidence in teaching, and this link needs to be explored in both domestic and OSPEX contexts.…”
Section: The Emerging Global Context Of Professional Culturementioning
confidence: 99%
“…However, relatively little is known about how to better prepare pre-service teachers for both the domestic and international teaching contexts (Leask, 2009; Thomas & Kearney, 2008), It would appear that while the teaching profession has become increasing globally mobile (Mahan & Stachowski, 1990;Proctor, Rentz & Jackson, 2001;Stachowski & Mahan, 1998;Thomas & Hill, 1994;) curricula at the tertiary level is not providing students with a teaching perspective that is flexible enough to be transferable from the Australian perspective to a more global outlook (Rivzi 2007). This situation has not gone unnoticed with reforms in teacher education continuing to call for innovative classroom experiences for prospective teachers (Ramsey Report, 2000;New South Wales Institute of Teachers, 2012).…”
Section: The Emerging Global Context Of Professional Culturementioning
confidence: 99%
“…These studies have shown that school classrooms are becoming increasingly diverse although teachers may not feel prepared to teach in diverse classrooms 15,16 . Indeed, the children in a classroom may vary in terms of demographic characteristics, presence or type of learning disability, cultural background, level of preparedness in a subject, interest in classroom material, and many other variables 14,17 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers who examine multicultural awareness, individuated instruction, and differentiated instruction have been able to demonstrate that the use of face-to-face teacher workshops combined online support (hybrid instruction) can raise a teacher's knowledge concerning diverse populations; can result in increased instructor confidence ratings related to teaching diverse populations; and enhances skills in teaching such populations 15,16 . Additionally, research suggests that the use of multi-age classrooms where students are not grouped according to their chronological ages and courses wherein students are unaware of their grades can result in higher test scores.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation